Accessibility of childcare facilities in the Brussels-Capital Region - Charlotte Casier; Anneloes Vandenbroucke; Jean-Michel Decroly; Pierre Marissal; Michel Vandenbroeck (Brussels Studies, 2025)
This study maps the accessibility of childcare facilities in the Brussels-Capital Region. It applies a multi-dimensional definition of accessibility, which takes geographical, financial, social, cultural and practical aspects into account as well as considering the application of priority rules. A doubly constrained gravity model exposed the differences in geographical and financial accessibility and formed the basis of a typology of childcare facilities. Subsequently, a survey was conducted among both French- and Dutch-speaking facilities, which served as a basis to enrich the typology. The study emphasises the need for more - many more – childcare places. These are especially needed in the west of the Region, and they should preferably apply means-tested rates to ensure that they are also accessible to single-parent families and jobseekers, for example. Finding childcare is also a challenge for parents with atypical working hours. The more facilities there are in areas where demand is much higher than supply, the more efforts they make with social and cultural accessibility.